Banana Chip Home Industry Development Strategy Using the Pentahelix Approach: An Islamic Economic Review - Medeni, Desi Chintiara; Marliyah; Yanti, Nursantri (Moneter: Jurnal Keuangan dan Perbankan, 2025)
The banana chip home industry in Sengon Sari Village faces challenges in business development despite having been in operation for decades. This study aims to identify development strategies for the banana chip home industry using a pentahelix approach with an Islamic economic perspective on the business owned by Mrs. Warsina in Sengon Sari Village. The research method used is qualitative, with data collection techniques involving interviews and observations of the five pentahelix stakeholders (academics, business operators, government, community, and media). Data analysis utilized the SOAR approach (Strengths, Opportunities, Aspirations, Results) to identify internal strengths and external opportunities. The research findings indicate that factors related to strengths and aspirations suggest a solid potential for development. The main strategies recommended include: developing an environmentally sustainable strategy, digital promotion, market access through e-commerce, sharia financial management training, and optimizing social media for transparent promotion. The implementation of these strategies aligns with the principles of Islamic economics, which emphasize justice, honesty, tawhid, and responsible leadership, thereby enhancing business competitiveness while benefiting the wider community.